PROSPEK PARTISIPASI PETANI DALAM PROGRAM PEMBANGUNAN HUTAN RAKYAT UNTUK MITIGASI PERUBAHAAN IKLIM DI WONOSOBO - Irawan, Evi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
Past experiences indicate that the success of many farm forestry projects is mainly influenced by farmerâs participation. Ex ante estimation of the likelihood of farmersâ participation in a particular farm forestry project might reduce the risk of project failure. This study aims to analyze ex ante, farmerâs participation in a hypothetical farm forestry project for climate change mitigation based upon a survey data of 117 farm forestry farmers in Tempurejo Village, Wonosobo Regency. Logit estimation suggests that the likelihood of a farmerâs participation is likely affected by age of farmer, education, farm household size and farmerâs experience in farm forestry business. Two policies implication of these findings are that government should increase farmersâ knowledge of climate change through extension programs, such as climate field school, and align the design of farm forestry projects for climate change mitigation with the prevailing farm forestry management system practiced by farmers.